Pengaruh Perilaku Kerja Dan Konflik Kerja Terhadap Kinerja Aparatur Desa Di Kecamatan Kewapante Kabupaten Sikka (Pada Desa Ian Tena, Desa Wairkoja, Desa Seusina Dan Desa Namangkewa) - Maria Aprilia; Maria Silvana Mariabel Carcia; Yosef Tonce (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
The background of this research aims: 1). To find out the work performance of apparatus in four villages 2). To analyze the effect of work behavior and work conflict on the performance of village officials. The population in this study were village apparatus in Kewapante District (In Ian Tena Village, Wairkoja Village, Seusina Village and Namangkewa Village), totaling 32 people. The population is limited, so this research was carried out by means of a census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and differential statistics, namely multiple linear regression. Hypothesis testing is done through the t test and f test. The results of the descriptive analysis show that the three variables are categorized as not good. The results of the t test statistics show that partially the work behavior variable has a positive and significant effect on the performance of the apparatus. The results of the t test statistics show that partially the work conflict variable has a negative and significant effect. The results of the f test statistics show that simultaneously the variables of work behavior and work conflict have a significant effect on work performance. The results of the determination analysis show that the two variables are able to explain the variation in the ups and downs of the performance of the village apparatus in Kewapante District (In Ian Tena Village, Wairkoja Village, Seusina Village and Namangkewa Village) of 28.5%.